Metamaterial-based dual-band microwave absorber with polarization insensitive and wide-angle performance - Mayank Agarwal, Mayank; Meshram, Manoj Kumar (American Institute of Physics Inc., 2018)
A polarization insensitive, wide angle low profile metamaterial absorber with dual-band absorption characteristics in C- and X-frequency bands is presented in this paper. The parametric variation is discussed in details to understand the dependence of absorption frequency and absorption level on the design parameters. The proposed structure supports the realization of near unity absorption at the two absorption frequencies independently by suitably varying the design parameters. The absorption mechanism is explained with the E-field and surface current distribution plots at the peak absorption frequencies. The absorption is due to the simultaneous excitation of electric and magnetic resonance in the structure. Constitutive electromagnetic parameters of the proposed structure are also retrieved and plotted against frequency. A sample of the proposed absorber is fabricated and measured response validates the numerical results. © 2018 Author(s)